Law Enforcement Problems Against Private Actors in Corruption Crimes in Indonesia - Rahman Rahman (Ilmu Hukum Prima (IHP), 2026)
The involvement of private actors in corruption crimes in Indonesia shows an increasingly complex trend along with increasing cooperation between the public and private sectors in the management of state finances and strategic projects. Although the Law on the Eradication of Corruption has provided a legal basis for the imposition of criminal liability on everyone, including private actors, law enforcement practices still face various obstacles, such as proving elements of unlawful acts, causal relationships with state financial losses, and the involvement of private actors which are often carried out through corporations or complex transaction schemes. This study aims to analyze the problems of law enforcement against private actors in corruption crimes in Indonesia and formulate efforts to strengthen a more effective law enforcement system. This study uses normative legal research methods with a statutory approach, a conceptual approach, and a case approach. The legal materials used consist of primary, secondary, and tertiary legal materials that are analyzed qualitatively. The results of the study show that law enforcement against private actors still faces various normative and practical obstacles, including the lack of optimal implementation of corporate criminal liability, the difficulty of proving the relationship between the actions of private actors and state financial losses, the weak tracing of assets resulting from criminal acts, and the lack of coordination between law enforcement agencies. Therefore, it is necessary to strengthen regulations, harmonize law enforcement policies, optimize asset recovery mechanisms, and increase the capacity of law enforcement officials so that the eradication of corruption involving private actors can be carried out more effectively, fairly, and provides legal certainty.